Architecture in its continuums constants ; manners, modes and qualities of engagement ; polarities and their origins - Van Schaik, Leon 1944- (Uro Publications, 2018)
This book is about the nature of architecture, its relation to society, and the ways in which it is practiced, researched, and taught